Rancang Bangun Peak Flow Meter dengan Output Suara dan Pemantauan Android - Patrisius Kusi Olla; Wilia Azhar (Aviation Electronics, Information Technology, Telecommunications, Electricals, Controls (AVITEC), 2021)
Peak Flow Meter (PFM) is a tool to measure the amount of air flow in the airway (PFR) and to detect asthma. The output value of PFR can be influenced by several factors, such as age, respiratory muscle strength, height and gender. In this research, airway measurements are used to measure the condition of patients suffering from asthma. The author aims to make this tool so that it can find out how to design and make a peak flow meter output sound tool, measure the peak current and can know how the MPXV7002DP sensor works in regulating output in the form of sound. The method used by the author is to design or make a tool peak flow meter output sound. This MPXV7002DP sensor works when the sensor receives air blows from the flow sensor which automatically reads the highest air pressure from the breath. The test results using the VT Mobile Medical Gas Flow Analyzer prove that the largest percentage error is 2.4%, with the blowing rate on the Peak Flow Meter is 64.0 lpm and the blowing rate on VT mobile is 62.50 lpm. Therefore, this tool can be said to be very certain to detect asthma. Then it can be concluded that the peak flow meter is feasible and meets the specified requirements.